Delayed Presentation of Dermatofibrosarcoma Protuberans in a Rural Healthcare Facility: A Case Report - Jeffrey,; Giri Yurista, (Jurnal Indonesia Sosial Sains, 2026)
Dermatofibrosarcoma Protuberans (DFSP) represents one of the rarest forms of soft tissue tumors, with an annual occurrence estimated at only 0.008 to 0.045 cases per 100,000 individuals. This rare, slow-growing but locally aggressive skin sarcoma often presents with subtle clinical features, leading to delayed diagnosis and management, particularly in resource-limited settings. In this report, we describe a case of DFSP that presented to a rural healthcare facility with delayed presentation. A 37-year-old woman was referred to the general surgery clinic with an enlarging lump in the calf of her left leg that had been present for the past 20 years. The lump had gradually increased in size and was initially painless. One month prior to hospitalization, the lesion became frequently painful, bled intermittently, and discharged pus. A wide excisional biopsy was performed, and the specimen was sent for histopathological analysis. The conclusion of the histopathological analysis was consistent with DFSP. This case highlights the diagnostic challenges of DFSP in resource-limited settings, where limited access to specialized diagnostic services, lack of awareness among primary healthcare providers, and financial constraints contribute to diagnostic delays. A long-standing lesion remained indolent before progressing to symptomatic disease, emphasizing the need for increased clinical vigilance in rural healthcare facilities. Early recognition and appropriate management are essential to improve patient outcomes.